STYLISTICS OF EROTIC WRITING BY FRÉDÉRIC BEIGBEDER - Bigun, O. A.; Kovbanyuk, M. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
Purpose. The paper is aimed at analyzing the erotic discourse of Frédéric Beigbeder's creativity as a component of aesthetics and poetics of post-postmodernism. Research methodology. Theoretical and methodological basis of the research based on the works of H. Marcuse, M. Merleau-Ponty, scientific works by psychoanalysts (S. Freud, A. Adler, C.-G. Jung), national issues on the aspect of erotic by V. Ageeva, L. Mudrak, N. Opryshko. Results. It is identified that brutality and crude sexismis a style feature of Beigbeder's works when sex being a direct physiological action formed the basis. On the other hand, Beigbeder's works reveal the complex relationship between libido and sublimation, the intensive search for their harmonization in the dramatic collisions of the biological and mental spheres of humaneistence. The stylistics of Beigbeder's erotic writing is distinguished by its specific emotionality, which is embodied in a wide palette of artistic means including metaphors, metonymies, words-realities, phraseological units, comparisons, vulgarisms, the inclusion of the imperative mood, etc. Originality. The paper shows the specific nature of the apology of human physicality referring to concrete examples in Beigbeder’s writings. Such a specificityleads to the particular interpretation of love based on cynicism as a means of saving in a world of lost, neglected values. Practical value. This paper can be used for further study of stylistic aspects of Beigbeder’s individual style (idiostyle). Research results can be useful during writing term papers, master’s ones and other scientific works.